Universal influenza virus vaccines: what needs to happen next?. (3rd July 2019) - Trucchi, Cecilia; Paganino, Chiara; Amicizia, Daniela; Orsi, Andrea; Tisa, Valentino; Piazza, Maria Francesca; Icardi, Giancarlo; Ansaldi, Filippo
ABSTRACT: Introduction : Influenza occurs worldwide and causes significant disease burden in terms of morbidity, associated complications, hospitalizations, and deaths. Vaccination constitutes the primary approach for controlling influenza. Current influenza vaccines elicit a strain-specific response yet occasionally exhibit suboptimal effectiveness. This review describes the limits of available immunization tools and the future prospects and potentiality of universal influenza vaccines. Areas covered : New 'universal' vaccines, which are presently under development, are expected to overcome the problems related to the high variability of influenza viruses, such as the need for seasonal vaccine updates and re-vaccination. Here, we explore vaccines based on the highly conserved epitopes of the HA, NA, or extracellular domain of the influenza M2 protein, along with those based on the internal proteins such as NP and M1. Expert opinion : The development of a universal influenza vaccine that confers protection against homologous, drifted, and shifted influenza virus strains could obviate the need for annual reformulation and mitigate disease burden. The scientific community has long been awaiting the advent of universal influenza vaccines; these are currently under development in laboratories worldwide. If such vaccines are immunogenic, efficacious, and able to confer long-lasting immunity, they might be integrated with or supplant traditional influenza vaccines.